Worked problems in heat, thermodynamics, and kinetic theory for physics students - Pincherle, L. (Leo) (Commonwealth and international library. Physics division., 1966)
Worked Problems in Heat, Thermodynamics and Kinetic Theory for Physics Students is a complementary to textbooks in physics. This book is a collection of exercise problems that have been part of tutorial classes in heat and thermodynamics at the University of London. This collection of exercise problems, with answers that are fully worked out, deals with various topics. This book poses problems covering the definition of temperature such as calculating the assigned value of the temperature of boiling water under specific conditions. This text also gives example of problems dealing with the fir.